From Thyroid Uptake to Molecular Imaging – A Journey of Nuclear Medicine in Bangladesh (Bangladesh Journal of Nuclear Medicine, 2017)
Abstract not availableBangladesh J. Nuclear Med. 18(1): 8, January 2015